Downstream process and characterization of probiomin for food and feed use - Bolo, Benjamin A., Jr. (Animo Repository, 2024)
The promotion and sustenance of good health is the aspiration of all local, national, and international communities. The upstream (UPS) and downstream (DSP) biotechnology processes are on the frontline of continuous product discovery to address this aspiration. The study offers a new Biotechnology product, a probiotic known as PROBIOMIN. Through DSP, four forms were produced, namely: PROBIOMIN Broth (PROB001), PROBIOMIN Paste (PROB002), PROBIOMIN Lyophilized Powder (PROB003), and PROBIOMIN Capsule (PRON004). The characteristics of these products were evaluated in terms of quality, safety, and applicability. There were no significant differences (P=0.3542) in viable cell counts among the four different forms when the products were stored at -10ºC, 4ºC, and 28ºC for 43 days. On batch samples, the four forms of PROBIOMIN obtained initial viable cell counts of log10 11 CFU/ml and were sustained at log10 7 CFU/ml when stored at 4oC for four (4) months. The Lactobacillus acidophilus BIOTECH strain 1900 used in producing PROBIOMIN showed good growth at pH 3. Likewise, it showed tolerance to bile salts at 0.3%, 0.5%, and 1% concentrations for up to five (5) hours that it was exposed, which is the minimum requirement for a probiotic. These show its potential to survive, withstand, and resist human and animal gut upon consumption The PROBIOMIN product had an aflatoxin content estimated at 5-9 ppb, which is considered safe based on the BFAD regulatory limit of 20 pbb. Significant changes in both the intracellular and extracellular fractions were observed during fermentation time from 0, 2,4, 36, and 48 hours using GC-MS. Through the variable importance in projection (VIP) score, six significant metabolites were detected in the intracellular fraction and four in the extracellular fraction. Most of these were organic acids, including lactic acid, which is the primary product of lactic acid fermentation. The PROBIOMIN (PROB003) was applied in the feeding trials of 36 hogs with four dietary treatments (T), as follows: standard farm feeds and standard vitamins (T1), standard farm feeds and commercial probiotics (T2), standard farm feeds and PROBIOMIN only (T3), and a standard farm feeds with a combination of commercial vitamins and PROBIOMIN (T4). These were evaluated based on the four key performance indicators (KPIs): average daily gain (ADG), feed conversion ratio (FCR), and % Morbidity and % Livability. Results in the ADG, FCR, and live weight with 0.68kg, 2.96, and 86.89 kg, respectively, were within the acceptable levels set by BAR. In addition, results showed that PROBIOMIN can be given as a feed supplement in lieu of the standard vitamins or the commercial probiotic product as indicated by the comparable results (P> 0.05) of T3 (PROBIOMIN only), T1 (vitamins) and ix T2 (commercial probiotics). Notably, the use of a combination of PROBIOMIN and vitamins in the feeds (T4) consistently gave significantly better results in the different KPIs tested than treatments with feeds and vitamins alone (T1). Morbidity ranging from 44% to 66.67% was noted among treatments during the starter and grower phases. However, no morbidity was recorded in the final phase. The feeding trials of PROBIOMIN, along with the other treatments, have sustained a total number of 36 hogs at the harvest period, indicating success with 100% livability for all treatments. ------------------------------------------------------------------------------------------------------------- Keywords: Probiotic, PROBIOMIN, Biotechnology, Lactic acid, Lactobacillus